Alberic the Wise and other journeys - Juster, Norton (Yearling, 1993)
Collects three stories of Renaissance Europe, including a man on an endless search for wisdom, a boy with no illusions, and the richest monarch in the world
Originally published: New York : Pantheon Books, 1965
Alberic the Wise -- She cries no more -- Two kings
Keywords: Wisdom / Fiction; Princesses / Fiction; Kings, queens, rulers, etc / Fiction; Renaissance / Fiction; Short stories; Kings and rulers / Fiction; Wisdom / Juvenile fiction